KINERJA ANGKUTAN UMUM BIS DAMRI DI BANDAR LAMPUNG - Rahayu Sulistyorini; Ofyar Z. Tamin (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2008)
Abstract The public transport service is very important for people who live in a city. The service is, therefore, to be maintained to satisfy the public transport users. This study aims to investigate the performance of bus service in the city of Bandar Lampung. The indicators used to measure the performance are those of the World Bandk. The results suggest that, in general, routes investigated have met the accessibility standards of the Worls Bank.Keywords: bus service, bus performance, and performance indicator.